Intensity noise mitigation in SAC OCDMA systems using a divided spectrum balanced detection scheme - Alhassan, A.M. (2013)
We propose the use of a divided spectrum balanced detection (DSBD) to reduce the intensity noise in spectral amplitude coding (SAC) OCDMA systems. Simulation results show several order of magnitude improvements in bit error rate (BER) compared to the conventional balanced detection. Â© 2013 IEEE.